Analyzing the Regulatory Role of the HigA Antitoxin within Mycobacterium tuberculosis - Fivian-Hughes, Amanda S. (American Society for Microbiology (ASM), 2010)
Bacterial chromosomally encoded type II toxin-antitoxin (TA) loci may be involved in survival upon exposure to stress and have been linked to persistence and dormancy. Therefore, understanding the role of the numerous predicted TA loci within the human pathogen Mycobacterium tuberculosis has become a topic of great interest. Antitoxin proteins are known to autoregulate TA expression under normal growth conditions, but it is unknown whether they have a more global role in transcriptional regulation. This study focuses on analyzing the regulatory role of the M. tuberculosis HigA antitoxin. We first show that the M. tuberculosis higBA locus is functional within its native organism, as higB, higA, and Rv1957 were successfully deleted from the genome together while the deletion of higA alone was not possible. The effects of higB-Rv1957 deletion on M. tuberculosis global gene expression were investigated, and a number of potential HigA-regulated genes were identified. Transcriptional fusion and protein-DNA-binding assays were utilized to confirm the direct role of HigA in Rv1954A-Rv1957 repression, and the M. tuberculosis HigA DNA-binding motif was defined as ATATAGG(N(6))CCTATAT. As HigA failed to bind to the next-most-closely related motif within the M. tuberculosis genome, HigA may not directly regulate any other genes in addition to its own operon.